Influence of the ortosano restoration method on chronic pain syndrome in degenerative-dystrophic diseases of the spine - Maliarenko, I. O.; Riznyk, O. I.; Маляренко, І. О.; Різник, Ольга Іванівна (My University, 2021)
Was to assess the influence and the effectiveness of complex physical rehabilitation using the ORTOSANO technique for people with degenerative-dystrophic diseases of the spine (DDS) on the severity of chronic pain (CHD). Materials and methods: We studied the condition of 166 patients. The observation group included patients with chronic pain caused by DDS of the spine. The patients underwent a course of complex physical rehabilitation in the center using the ORTOSANO method. Results: The following results were obtained statistically: pain with localization in the lumbosacral spine was registered in 67 patients (40.4%), in the cervical spine – in 42 patients (25.3%), in the thoracic spine – in 37 patients (22.3%). Pain in the shoulder joints was registered in 24 patients (14.5%), in the hip joints in 16 (9.6%), knee joints – in 12 (7.2%), in the ankle joints – in 9 patients (5.4%). Initially, the level of pain among all the group members according to the VAS scale was on average (7.6 ± 0.35) points in men and (6.4 ± 0.72) in women (p <0.05). Conclusions: 1.It was established that the proposed complex physical rehabilitation using the ORTOSANO method reduces the severity of chronic pain significantly, improves functional and daily activity, quality of life, and stabilizes the neuro-psychological state of patients. 2. The ORTOSANO method can be recommended to be used in the complex of rehabilitation exercises in physiotherapeutic departments of educational and medical establishments.
Keywords: chronic pain syndrome; physical rehabilitation; quality of life; neuropsychological status